Recording, Reporting, and Utilizing School Attendance Data in Sweden, Finland, Denmark, and Norway: A Nordic Comparison - Maria Sandhaug; Iines Palmu; Sarah Jakobsen; Johan Strömbeck; Maren-Johanne Nordby; Peter Friberg; Jenny Berg; Lotte Fensbo; Jenny Sjöström; Mikael Thastum (Karolinum Press, 2022)
The compulsory educational context and school systems within the Nordic countries Sweden, Finland, Denmark, and Norway share fundamental similarities, facilitating comparison across these countries. In this study, we describe and compare existing practices of recording, reporting, and utilizing school attendance data in four countries. In Sweden, Finland, and Norway there is a lack of national guidelines and agreements of how to record, report, and use school attendance data. Municipal autonomy has led to a variety of recording and reporting practices, which then lead to lack of comparable data and wider use of the data gathered. Denmark has a national registry of attendance data, and schools are required to report the data to municipal level. There are more specific guidelines regarding recording and reporting in Denmark compared to Sweden, Finland, and Norway. Problems with school non-attendance are well recognized in the North, but ways of recording and responding to absenteeism are still versatile. This leads to inconsistencies both within and between the countries. Due to variations of the way attendance is recorded, the quality of the national registry of data in Denmark can be questioned. A unified approach to inform research and practice to include formalized definitions of school absence in the Nordic Education Acts are suggested. It requires schools to record and report attendance data within a national register and finding a reliable way to differentiate problematic from non-problematic absenteeism.